The Effect of the FIFA 11+ Kids Warm-Up Training Program on Lower Limb Injury Prevention and Football Player Performance (A Systematic Review) - Adeleh Eslami; Mansour Sahebozamani; Saeid Bahiraei (Biyumikānīk-i varzishī)
Objective TFootball is one of the sports with the highest risk of injury, with children suffering injuries at a rate of approximately 3% yearly and major injuries at a rate of approximately 0.69%. The aim of this systematic review is to examine the effects of the FIFA 11+ Kids program on injury prevention and performance improvement in preadolescent soccer players. Methods This review aims to gather research conducted between 2016 and 2022 pertaining to the subject of research. The present investigation uses Scopus, Google Scholar, PubMed, and Science Direct databases to perform a comprehensive search for pertinent research. The search is conducted using keywords including FIFA 11+ Kids, prevention, children, injury, lower limb, performance, and anterior cruciate ligament. Results Thirty publications were retrieved using the search strategy, and thirteen were chosen for finalization and inclusion in this study based on the criteria for inclusion and exclusion. The implementation of FIFA 11+ Kids exercises in children has been shown to enhance physical fitness components such as balance, jumping activities, lower limb isokinetic strength, and knee joint proprioception. Furthermore, these exercises have been found to mitigate injuries, particularly in the lower limb, and significantly decrease associated treatment expenses. Conclusion Research indicates that the FIFA 11+ Kids warm-up training program plays a unique role in preventing lower limb injuries and improving performance, particularly if performed over an extended duration or with more training sessions per week. Therefore, it is imperative to implement this training program for football players under 14 years of age.